Response to selection for grain yield and correlated response for grain size and earliness in cowpea based on early generation testing - Padi, Francis K (Wiley, 2008)
Large grain size and earliness to flowering are traits critical to cowpea adoption in the West African savannahs. This study reports on the correlated response to selection in these two traits in the two populations in which selections were made primarily for grain yield potential. Further, the present study reports on the effectiveness of early generation selection for grain yield. Each of the two populations, SARC 2 and SARC 3, was derived from a cross between an adapted parent Marfo‐Tuya and an exotic breeding line that has large grain size and early flowering. Replicated yield evaluation of F5 families showed that grain yield of Marfo‐Tuya was not different from those of the highest yielding families in each population. Increases in grain size of individual families over Marfo‐Tuya were large and, the response to selection averaged 5.3 and 3.9 g/100 seeds in the SARC 2 and SARC 3 populations, respectively. Response to selection in days to flowering averaged 3 days in SARC 3, whereas response to selection was not observed in SARC 2. Retrospective selection in the F3 at 40% intensity was efficient in identifying a high proportion of elite families in each population.